2010
DOI: 10.1111/j.1462-2920.2010.02331.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory exaptation of the catabolite repression protein (Crp)–cAMP system in Pseudomonas putida

Abstract: The genome of the soil bacterium Pseudomonas putida KT2440 encodes singular orthologues of genes crp (encoding the catabolite repression protein, Crp) and cyaA (adenylate cyclase) of Escherichia coli. The levels of cAMP formed by P. putida cells were below detection with a Dictyostelium biosensor in vivo. The cyaA(P. putida) gene was transcribed in vivo but failed to complement the lack of maltose consumption of a cyaA mutant of E. coli, thereby indicating that cyaA(P. putida) was poorly translated or rendered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
76
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(78 citation statements)
references
References 81 publications
1
76
0
1
Order By: Relevance
“…We therefore concluded that the crp gene product is involved in the utilization of these aromatic amino acids as nitrogen sources. These results are in agreement with those reported by Milanesio et al (27), which showed that crp mutations do not affect the panel of C compounds that can be used by P. putida as growth substrates and that a crp mutant was impaired in the use of certain dipeptides as an N source.…”
Section: Maximal Expression Of the Phhab Operon Requires Crp And Campsupporting
confidence: 83%
See 2 more Smart Citations
“…We therefore concluded that the crp gene product is involved in the utilization of these aromatic amino acids as nitrogen sources. These results are in agreement with those reported by Milanesio et al (27), which showed that crp mutations do not affect the panel of C compounds that can be used by P. putida as growth substrates and that a crp mutant was impaired in the use of certain dipeptides as an N source.…”
Section: Maximal Expression Of the Phhab Operon Requires Crp And Campsupporting
confidence: 83%
“…In contrast with other microorganisms, it should be noted that the characterization of a P. putida crp-deficient mutant revealed that the profile of C sources used by this mutant is identical to that of the wild-type strain (8,27). In P. putida, the crp gene product (PP0424) is annotated as a cyclic AMP (cAMP) receptor protein, with high similarity to Crp of Escherichia coli (62% identity) and Vfr of Pseudomonas aeruginosa (82% identity).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Por ejemplo, el plumaje apareció en su momento como un mero aislamiento térmico pero luego se transformó en un componente esencial del vuelo de los pájaros. El análisis de los genomas bacterianos proporciona incontables ejemplos de proteínas que nacen para hacer algo que luego resulta ser muy distinto de aquello para lo que finalmente se utilizan (Milanesio et al, 2011). Este proceso, que en Biología evolutiva se denomina exaptación, tiene también incontables equivalentes en ingeniería: un dispositivo que se inventa con un propósito muy específico reaparece con pequeñas modificaciones en otro sitio con una finalidad inesperada e incluso opuesta a la inicial.…”
Section: Tecno-logía Vs Tecno-nomíaunclassified
“…As it is known, in many cases catabolite repression in microorganisms is correlated with lowered levels of cAMP [ 8,12,13 ]. Our present results (Table 1) illustrate the reversal effect of cAMP on SOD synthesis by H. lutea cells in the presence of glucose.…”
Section: Fig 3 Deinduction Of Sod Synthesis By Removal Of Cu Ionsmentioning
confidence: 99%